(untitled) (Research, Society and Development, 2022)
This study aims to contribute to the construction of knowledge through the development of a prototype and content validation of a technological resource for the care of diabetic pregnant women using insulin. This is a validation research of an application on insulin use orientation. This process occurred at the Fernando Magalhães Maternity Hospital. The study sample was of the non-probabilistic type, selected by convenience, formed by medical professionals (2) and nurses (8), specialized in obstetrics. Data was collected using a self-administered questionnaire. The answers were organized in a database built in Microsoft Excel and analyzed by the Likert-type rating scale. After compiling the data in a spreadsheet, it was exported to the program R version (4.0.2© 2020-06-22), free software for the elaboration of statistics, where univariate analyses were performed. According to the evaluation of the judges expressed in the statements, it confers the acceptance of the App content, making the application "insugest" suitable for the proposed objectives contributing to the process of health education. As a future work, it is necessary to evaluate the impact of this technology as a resource for the discharge plan of women diagnosed with diabetes.